PREVENTION OF SCALE IN THE DOWNHOLE EQUIPMENT AND PRODUCTIVE RESERVOIR DURING THE OIL WELL OPERATION - Saychenko , Liliya; Tananykhin , Dmitry; Ashena , Rahman (Journal of Applied Engineering Science, 2020)
The problem of scale is very common in the process of oil production at the initial and the final stages of field development. Inorganic scale may precipitate from the formation fluids in various elements of the oilfield system in the oil extraction process. These scales, which collect under certain thermodynamic and physical-technical conditions, cause a decrease in equipment reliability and productivity. The article highlights the main factors affecting the process of scale in field conditions, and evaluates the effectiveness of scale inhibitors. It is noted that at wells with periodic inhibition, it is necessary to switch to more modern protection technologies – constant dosing of the inhibitor into the annulus and setting the inhibitor in the bottom hole formation zone.
Keywords: scale, scale inhibitor, co-produced water, bottom-hole formation zone, supersaturation